Hybrid inverter arrangements to facilitate reduced switching losses of the main inverter - Klumpner, Christian; Zargar, Tanzeel (2016)
This paper investigates two hybrid inverter topologies consisting of a slow switching DC/AC main voltage source inverter and output series connected low-voltage rated, fast switching auxiliary inverters that may be suitable for medium and high voltage AC grids. Two topologies of auxiliary inverters are investigated: the use of AC choppers implemented with bidirectional switches as well as using the more traditional H-bridge inverter. A modified modulation scheme for the main inverter enables the elimination of the zero voltage vectors which allows the use of only two switchings per switching period which may reduce significantly the associated switching losses. As the result is a quasi-trapezoidal output phase voltage, the auxiliary inverters are controlled to remove the differential mode distortion. Simulation results prove that the proposed hybrid grid interface is able to provide low harmonic voltage content.